Mapping the Landscape of Doctoral Research in Technologies in Education: A 25-Year Analysis in Portuguese Universities - Fernando Albuquerque Costa; Elisabete Cruz (MDPI AG, 2023)
In the context of the evolving landscape of doctoral education within the framework of a knowledge society, this study explores the landscape of doctoral research in the field of technologies in education (TE) within Portuguese universities. The investigation places its focus on understanding the composition and evolution of research themes over 25 years (1997-2022), unveiling the landscape's responsiveness to the challenges of a technologically advanced society. Employing a scientometric approach, we analyse 380 doctoral dissertations, highlighting the authors' nationalities and genders, as well as the burgeoning themes, research questions, and methodological frameworks. Our results reveal a diverse range of themes, with "Teaching and Learning" and "Professional Development" emerging as predominant areas of exploration. Researchers predominantly derive their problems from real educational contexts, seeking to enhance understanding and intervention. This study underscores a shift from a technology-centric perspective to one focused on pedagogical considerations. Through this article's objective representation, our findings highlight the multifaceted nature of TE research in Portuguese universities and its implications for innovation and knowledge advancement in education.